Elevated Serum Gastrin Is Associated With a History of Advanced Neoplasia in Barrett’s Esophagus - Wang, Judy S. (2009)
OBJECTIVES: Proton pump inhibitors (PPIs) are frequently prescribed to patients with Barrett’ s esophagus (BE), but in a subset, they can induce significant hypergastrinemia. Elevated levels of gastrin have been associated with tumorigenic effects in a number of gastrointestinal cancers. We decided to investigate the association between serum gastrin levels and dysplasia in BE. METHODS: We performed a cross-sectional study and enrolled patients with BE without dysplasia, low-grade dysplasia (LGD), high-grade dysplasia (HGD), or adenocarcinoma (AC), as well as gastroesophageal reflux disease controls, all chronically taking PPIs. Fasting serum gastrin was measured, and data were collected on patient characteristics, medication use, and the highest degree of BE neoplasia. RESULTS: A total of 95 patients were enrolled. The mean age was 64.7 (±10.0) years, and 70.5 % were male. The median serum gastrin level was 40 pM. There was no significant difference in gastrin levels with increased degrees of BE neoplasia (overall P = 0.68). In multivariable analysis, the highest quartile of gastrin was associated with significantly increased odds of advanced neoplasia (HGD or AC) (odds ratio (OR): 5.46, 95 % confidence interval (CI): 1.20–24.8). CONCLUSIONS: In BE patients taking PPIs, an elevated serum gastrin is associated with a history of HGD or AC. Prospective studies are needed to determine whether patients with nondysplastic BE and elevated serum gastrin are at increased risk for neoplastic progression.